2019
DOI: 10.1038/s41598-019-56615-4
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation as a predictor of acute kidney injury and mediator of higher mortality after acute kidney injury in non-cardiac surgery

Abstract: This retrospective cohort study examined the roles of inflammation in acute kidney injury (AKI). Serum albumin and C-reactive protein (CRP) were used as markers of inflammation. Adults who underwent non–cardiac surgery from 2007 to 2011 were included. Exclusion criteria were urological surgery, obstetric surgery, missing data, and pre-operative dialysis. Subjects were followed until the end of 2015 or loss to follow-up. Associations between pre–operative albumin or CRP and post-operative AKI or association bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 25 publications
1
29
1
Order By: Relevance
“…Thus, high CRP levels could identify patients more prone to organ dysfunction, including kidney failure. High CRP level was associated with AKI in other diseases as well [ 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, high CRP levels could identify patients more prone to organ dysfunction, including kidney failure. High CRP level was associated with AKI in other diseases as well [ 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Acute kidney injury (AKI) is a severe manifestation of COVID-19 (see Table 1 ). As with other pathologies, inflammation plays a central role here as well and is the main subject of the various research studies on AKI [ 116 , 117 ].…”
Section: Xylose/xylitol Hypertension Acute Kidney Injury Coronary mentioning
confidence: 99%
“…However, one possible underlying mechanism is likely related to in ammation. A previous study showed that in ammation is a predictor of postoperative AKI and a mediator of increased mortality after AKI in noncardiac surgery [25]. However, perioperative parecoxib reduced local and systemic in ammatory cytokines postoperatively [26,27].…”
Section: Discussionmentioning
confidence: 95%